The moviment body language and children education: A playful formative experience - Zanotto, Luana; Ferreira, Bruno Martins; Alves, Fernando Donizete [UNESP] (Associacao Pro-Ensino Superior em Novo Hamburgo, 2020)
This article reports the learning from short duration training about movement body language and the children education. It aimed to socialize the teacher's knowledge and skills to organize the proposition of body playful activities in the pedagogical practices. From Physical Education teachers to educators, the training showed the practice of activities and created comprehension of body language combined with playfulness, as well as reflections on how to make it more meaningful in pedagogical interventions. The training analyzes showed the participants' appreciation for recognizing the potential of play in children's development. It ended with reflections on the playful pedagogical practices that can be enjoyed in childhood. Moreover, it was finished with perceptions about the way of educator's basic training and continued education for acting children's motricity, that require differentiated and contextualized actions to the childcare workers profile.
A linguagem corporal de movimento e a educação infantil: Uma experiência lúdico-formativa
Keywords: Children education; Pedagogy course; School physical education; Teacher training